2018
DOI: 10.2478/fhort-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and biochemical analyses of in vitro drought stress response in ornamental European Bluestar (Amsonia orientalis Decne.)

Abstract: This study aimed to investigate the effects of drought stress on Amsonia orientalis, an endangered ornamental plant with a limited natural distribution in Europe. Effects of polyethylene glycol (PEG)-mediated drought stress (-0.15, -0.49, -1.03 and -1.76 MPa osmotic potentials) were tested on in vitro cultures. In general, root lengths and numbers, total protein, chlorophyll a and carotenoid contents were negatively influenced at elevated levels of the stress factor. The successive decrease in the tested osmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
5
3
0
2
Order By: Relevance
“…The highest PEG concentration (7%) caused the biggest decrease in shoot length (11.5 ± 0.43 mm), which was statistically different from that of the control (48.3 ± 2.68 mm) and the PEG concentration 2% ( Table 1 ). Similar results were obtained in in vitro cultures of Thymus vulgaris [ 4 ], Thymus citriodorus [ 7 ], Salvia leriifolia [ 46 ], Stevia rebaudiana [ 3 ], and Amsonia orientalis [ 47 ], under drought stress. When plants are subjected to drought stress, the water movement through the xylem decreases, and to maintain turgor status plant cells have to reduce their osmotic potential [ 47 ].…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The highest PEG concentration (7%) caused the biggest decrease in shoot length (11.5 ± 0.43 mm), which was statistically different from that of the control (48.3 ± 2.68 mm) and the PEG concentration 2% ( Table 1 ). Similar results were obtained in in vitro cultures of Thymus vulgaris [ 4 ], Thymus citriodorus [ 7 ], Salvia leriifolia [ 46 ], Stevia rebaudiana [ 3 ], and Amsonia orientalis [ 47 ], under drought stress. When plants are subjected to drought stress, the water movement through the xylem decreases, and to maintain turgor status plant cells have to reduce their osmotic potential [ 47 ].…”
Section: Resultssupporting
confidence: 74%
“…Similar results were obtained in in vitro cultures of Thymus vulgaris [ 4 ], Thymus citriodorus [ 7 ], Salvia leriifolia [ 46 ], Stevia rebaudiana [ 3 ], and Amsonia orientalis [ 47 ], under drought stress. When plants are subjected to drought stress, the water movement through the xylem decreases, and to maintain turgor status plant cells have to reduce their osmotic potential [ 47 ]. The decrease in shoot length could be explained by the restricted water absorption and the turgescence pressure for cell enlargement, which disrupt cell division and elongation [ 46 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Increasing POD activity was also reported in Glycine max (50) and Triticum aestivum (51) after Mo and Zn treatments, respectively. In a recent study on A. orientalis, it was shown that elevated POD activity and nearly unchanged CAT activity catalyzed the transformation of H 2 O 2 to H 2 O and protected the plant against drought stress (5). The increases in POD and CAT activities after Zn/Mo exposure were more pronounced than was found following salt and drought stresses in A. orientalis (4).…”
Section: Discussionmentioning
confidence: 95%
“…The decrease in its habitat may be related to anthropogenic and/or environmental abiotic factors. To investigate the effects of salt and drought stress on the growth and physiology of A. orientalis, several studies have been conducted (4,5). However, the effects of heavy metal contamination, which is a major global environmental problem, on A.…”
Section: Introductionmentioning
confidence: 99%